Prevalence and role of risk factors for hypertension in 18-69 years of age in rural and urban areas of district Amritsar, Punjab, India - Mitra, Chasham; Lal, Mohan; Singh, Tejbir; Deepti, S. S. (International Journal Of Community Medicine And Public Health, 2017)
Background: Hypertension is a major public health problem in India and its prevalence is high among rural and urban population. All the risk factors of lifestyle are known to cause the early onset and rapid worsening of hypertension. Methods:A cross sectional study was conducted. 1000 participants (500 rural and 500 urban) between the age group of 18-69 years were selected by systematic random sampling method from 5 villages and 5 urban wards of Amritsar city. Out of total, 500 males and 500 females were selected. Results: This study shows that 332 (33.2%) participants were hypertensive out of total 1000. The chances of Hypertension are directly proportional to age and shows peak between 50-59 years of age, 86 (59.72%). The prevalence among males and females was 32.4% and 34% respectively. Hypertension is highest in respondents with body mass index (BMI >30) i.e. 53.43%. The prevalence of hypertension was slightly higher among smokers than non-smokers and among vegetarians than non- vegetarians. Conclusions:Hence, it becomes necessary to adopt a lifestyle with regular physical activity for at-least 30 min a day, for 5 days of the week, to decrease prevalence of obesity and to maintain BMI within normal range. Thus awareness among communities should be raised regarding prevention of the risk factors for hypertension.